1993
DOI: 10.1016/0014-5793(93)81805-a
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy in juvenile visceral steatosis (jvs) mice with systemic carnitine deficiency

Abstract: We have reported the clinical and biochemical findings in juvenile visceral steatosis (jvs) mice with systemic carnitine deficiency. This paper is the first report about cardiomyopathy injvs mice. Adult jvs mice (at the age of 2 3 months) show cardiac hypertrophy which is caused by enlargement of the cardiac muscle cell associated with increases of non-collagen protein and DNA content. Carnitine administration (2 mg/head, twice a day, from 1 month of age) significantly suppresses the cardiac hypertrophy, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 27 publications
(29 reference statements)
2
40
0
Order By: Relevance
“…Role of carnitine in brown adipocytes K Ozaki et al and display a severe carnitine deficiency and the accumulation of lipid droplets in various cells (hepatocytes, renal tubular epithelial cells, cardiac myocytes, and striated myocytes). [12][13][14]17 L-carnitine administration increases the carnitine concentration and eliminates the accumulation of lipids in the liver, heart, and skeletal muscle of JVS mice. 12,14,17,26 However, tissue carnitine levels in the heart, liver, and skeletal muscle are significantly lower than those in controls, even after L-carnitine administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Role of carnitine in brown adipocytes K Ozaki et al and display a severe carnitine deficiency and the accumulation of lipid droplets in various cells (hepatocytes, renal tubular epithelial cells, cardiac myocytes, and striated myocytes). [12][13][14]17 L-carnitine administration increases the carnitine concentration and eliminates the accumulation of lipids in the liver, heart, and skeletal muscle of JVS mice. 12,14,17,26 However, tissue carnitine levels in the heart, liver, and skeletal muscle are significantly lower than those in controls, even after L-carnitine administration.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]17 L-carnitine administration increases the carnitine concentration and eliminates the accumulation of lipids in the liver, heart, and skeletal muscle of JVS mice. 12,14,17,26 However, tissue carnitine levels in the heart, liver, and skeletal muscle are significantly lower than those in controls, even after L-carnitine administration. 26 According to these previous reports, the effects of L-carnitine administration seem to differ among various organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9) Horiuchi et al reported that carnitine administration corrected growth retardation and abnormal gene expression of urea-cycle enzymes and was partly effective in ameliorating the fatty liver and in suppressing the cardiac hypertrophy. 10,11) These results indicate that carnitine deficiency plays an important role in the development of these pathological features. At present, JVS mice are recognized as a novel animal model for human systemic carnitine deficiency.…”
mentioning
confidence: 82%